Management of HBV- and HCV-induced end stage liver disease. (12th April 2012) - Mutimer, David J; Lok, Anna
Abstract : Hepatitis B and hepatitis C infections are important causes of end-stage liver disease and primary liver cancer. Successful antiviral treatment prior to the development of cirrhosis will prevent most of the morbidity and mortality associated with those infections. This can be achieved for a high proportion of patients. However, many patients present with end-stage liver disease and ongoing and clinically significant viral replication. Antiviral treatment of HBV can effect recovery of liver function and restores many patients to a state of well compensated cirrhosis. The antiviral treatment of end-stage HCV poses much greater challenges. Interferon remains an essential element of HCV antiviral treatment, but has reduced efficacy and significant toxicity at this stage of cirrhosis. Though yet to be evaluated in the setting of advanced liver disease, the development of direct acting antivirals for HCV offers hope for improved outcomes at this stage of cirrhosis.